Suffering as a Lifelong Companion: A Phenomenological-Hermeneutic Study of Men Living With Severe Psychiatric Illness - Anne Kasén; Terese Bondas (SAGE Publishing, 2022)
Accumulation of suffering in later life due to severe psychiatric illness has received surprisingly little interest in nursing research. Suffering in daily living seems to be more demanding for men, a phenomenon still debated in the literature. This phenomenological-hermeneutic study aims at describing and interpreting the perspectives of adult men and their experiences of suffering in daily living with severe psychiatric illness, diagnosed as schizophrenia. Data were collected in dialogical conversations with four men aged between 20 and 40 years, living alone in northern Norway. The themes created from the structural understanding illuminate the participants' suffering as simultaneously struggling against the grasp of the illness and for reshaping the future. The theoretical interpretation unfolds the multidimensionality of their suffering and the need for confirmation of the suffering and reconciliation with the losses from illness, thus making reorientation to the future possible.